2024
DOI: 10.3389/fpsyg.2024.1403661
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Innovations in teaching and learning: international approaches in developing teacher education and curriculum for the future

Markus Talvio,
Marco Ferreira,
Lawrence Meda

Abstract: April CITATIONTalvio M, Ferreira M and Meda L ( ) Editorial: Innovations in teaching and learning: international approaches in developing teacher education and curriculum for the future. Front. Psychol. :. doi: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Fortunately, many educational researchers have realized the significance of using experiments to find the most suitable teaching methods for students, rather than just following authority or mainstream. For example, He and Oltra Massuet evaluated learners' grammar sensitivity and language production ability through oral imitation task tests to construct English problems with fine grammar errors [59]. For another example, Ayabe et al studied the value of charts in mathematics teaching and found that including charts that are suitable for problems can help improve student problem-solving performance and reduce cognitive burden in problem-solving activities [60].…”
Section: Inspiration For Educationmentioning
confidence: 99%
“…Fortunately, many educational researchers have realized the significance of using experiments to find the most suitable teaching methods for students, rather than just following authority or mainstream. For example, He and Oltra Massuet evaluated learners' grammar sensitivity and language production ability through oral imitation task tests to construct English problems with fine grammar errors [59]. For another example, Ayabe et al studied the value of charts in mathematics teaching and found that including charts that are suitable for problems can help improve student problem-solving performance and reduce cognitive burden in problem-solving activities [60].…”
Section: Inspiration For Educationmentioning
confidence: 99%
“…Fortunately, many educational researchers have realized the significance of using experiments to find the most suitable teaching methods for students, rather than just following authority or mainstream. For example, Talvio et al evaluated learners' grammar sensitivity and language production ability through oral imitation task tests to construct English problems with fine grammar errors [59] . For another example, Cao et al studied the value of charts in mathematics teaching and found that including charts that are suitable for problems can help improve student problem-solving performance and reduce cognitive burden in problem-solving activities [60] .…”
Section: Inspiration For Educationmentioning
confidence: 99%